Mobile App Qc Pass Lahan pada Proyek: Studi Kasus : PT. Home Center Indonesia - Dzaky Setiawan Tauri; Muhammad Rizky Albaras; Samsudin Samsudin; Wasis Haryono (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
In the rapidly evolving digital era, the use of mobile applications has become a fundamental necessity across various sectors, including the construction industry. PT Home Center Indonesia, which specializes in providing and installing furniture for building projects, faces challenges in the QC Pass Land recording process, which is currently done manually. This practice poses risks of data loss, miscommunication with vendors, human errors, and data invalidity, ultimately disrupting work efficiency. This study aims to develop a mobile application to replace the manual recording system in the QC Pass Land process for the Sky House BSD project. The application is designed to enhance the efficiency, accuracy, and reliability of data recording while minimizing the risk of information loss through the implementation of a structured digital system. Additionally, the application is equipped with a feature that allows the inclusion of photo evidence, thereby improving data validity. The results of developing this mobile application are expected to accelerate the recording and furniture installation process, reduce the time required for data verification, and provide a solution that can be implemented in future projects. Through this practical work, the implementation of the application is anticipated to run effectively and contribute significantly to improving the QC Pass Land process at PT Home Center Indonesia.